The Use of E-Learning in Maritime English Learning Can Improve the Vocabulary Skill of Cadets Majoring in Electro-Technical Officer Shipping - Tekat Sukomardojo; Dyah Ratnaningsih (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: The increasingly global trade in the world demands the sea transportation industry, especially ships, to further increase the capabilities and expertise of the crew, especially the ability to communicate in English. So in the national education system, learning English is very important. . Design/methodology/approach: Various methods are used to improve English language skills, one of which is the use of technology in learning for students, namely by using e-learning. Findings: This study aims to determine the use of e-learning in maritime English learning, one of which can improve the vocabulary skills of cadets majoring in Eto Pelayaran and to find out the obstacles that might occur when using e-learning in learning English maritime eto shipping. Research limitations/implications: This study uses a quantitative approach with the analysis used is descriptive-quantitative analysis that reveals the problems that occur Practical implications: The sample of this study was 25 cadets in the ETO Shipping class in Semester II, totaling 25 people. Originality/value: This research conducted at the ETO Shipping class in Semester II. Paper type: This paper can be categorized as a Study cases